Senses and Capital Punishment: The Execution Preaching of Juan Gascó, 1787–1801 - Gomis, Juan (Renaissance and Reformation / Renaissance et Réforme, 2025)
Public executions in early modern Europe were shocking spectacles designed to impress the crowds who witnessed them. They were a manifestation of justice and the power of the state and had an exemplary purpose, so they were conceived as performances with a theatrical dimension that sought to stimulate the senses of the public. As far as the prisoners were concerned, they were expected to accept their collective fate and not to panic during the ritual of punishment, and thus to die a good death. They could only achieve this by trying to suspend their senses and thereby cushion the impact of the spectacle of which they were the protagonists. Comforters and priests were in charge of helping and preparing prisoners in the hours leading up to the execution. In seeking to understand this tension between stimulation and inhibition of the senses, this article analyzes an extraordinary unpublished source on public executions in Valencia at the end of the eighteenth century: the sermons and exhortations of the priest Juan Gascó, who assisted those condemned to death in the city between 1787 and 1801.